Pengaruh Kepemilikan Manajerial, Konservatisme Akuntansi, dan Asimetri Informasi terhadap Manajemen Laba pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2017-2019 - Fidelia; Kenny Ardillah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of managerial ownership, accounting conservatism, and information asymmetry on earnings management. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. In this study, the sample used was a manufacturing company listed on the Indonesia Effect Exchange for the 2017-2019 period with a total population of 183 companies. With purposive sampling technique, get 28 companies as a sample. This study uses a panel data regression method with a general effects model approach using Eviews 10. The results of this study indicate that information asymmetry has a negative effect on earnings management while managerial ownership, accounting has no effect on earnings management.